Management of cucumber downy mildew with fungicides - Ghosh, Diptanjan; Bhattacharya, Indrabrata; Dutta, Subrata; Saha, Abhijit; Majumdar, Debasis (Indian Journal of Plant Protection, 2020)
The study was conducted during 2010-2011 to find out the incidence of downy mildew of cucumber caused by Pseudoperonospora cubensis and evaluate the effectiveness of fungicides in controlling the disease. The fungicide trial was conducted with 8 fungicides, viz., fosetyl-al, dimethomorph, cymoxanil-mancozeb, copper oxychloride, metalaxyl-mancozeb, propineb, mancozeb, chlorothalonil and a control without application of any fungicides at research farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal. High humidity (RH> 93%) and slightly lower minimum temperature (18-25oC) and light rain during last week of october triggered the initiation of downy mildew disease of cucumber and high humidity in the region spread the disease quickly and pdi (per cent disease intensity) reached >50% within a month of disease initiation. Logistic equation was better to represent disease progress curve (r2 = 0.96, and se = 0.055) than linear equation (r2 = 0.91, se = 0.114). The result of field trial with fungicides against downy mildew of cucumber established that final pdi and audpc (area under disease progress curve) in the following order of these fungicides treatments: Fosetyl-al < dimethomorph < cymoxanilmancozeb < copper oxychloride < metalaxyl-mancozeb < propineb < mancozeb < chlorothalonil and highest in control untreated plots. Among the eight fungicides, systemic fungicides, fosetyl-al followed by dimethomorph and cymoxanil-mancozeb were found to be effective in reducing disease incidence and enhancement of yield.